Democracy in social movements - Porta, Donatella Della (ed.) (London, 2009)
This collection explores how principles and practices of democracy are elaborated and implemented within the global justice movement, both in their internal organization and in experiments of public decision-making. The issue of internal democracy is particularly relevant for a multifaceted and heterogeneous movement which has denounced the democratic deficits of decision-making processes and stressed the need for radical democratic reforms. In addition, and in part as a response to these demands for greater levels of citizen participation, experiments in participatory and deliberative forms of democracy are underway. Taking an empirical perspective, this collection investigates the development of new conceptions and practices of democracy, integrating research into approximately 250 European and transnational social movement organizations.
Keywords: Social movement